2004
DOI: 10.1373/clinchem.2003.030379
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Nonradiometric Method for Determining Thymidine Kinase 1 Activity

Abstract: Conclusion:The TK1 enzyme-labeled immunoassay uses a stable substrate, is precise, appears to be accurate, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
1
27
0
1
Order By: Relevance
“…The reaction is performed at 37 • C in a 0.1 M sodium acetate phosphorylation buffer supplemented with enzyme co-factors and stabilizing reagents [11,23]. ATP serves as a phosphate donor in the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction is performed at 37 • C in a 0.1 M sodium acetate phosphorylation buffer supplemented with enzyme co-factors and stabilizing reagents [11,23]. ATP serves as a phosphate donor in the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, TK1 can phosphorylate nucleotide analogs with modifications at the 5 -position of the pyrimidine ring, and the 3 -position of the ribose including 5-fluoro-2 -dideoxythymidine and 3 -azido-3 -deoxythymidine (Zidovudine) [9,10]. These nucleotide analogs can therefore be used to monitor the activity of TK1 [3,6,11]. For example, 18 F-3 -deoxy-3 -fluorothymidine ( 18 F-FLT), has been used to monitor tumor proliferation via positron emission tomography [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Проводилось сравнение тест-систем для выявления ТК-1, изучалась корреляция между сыворо-точной концентрацией и активностью ТК-1 при различных ЗНО и в норме [15][16][17][18].…”
Section: тк-1 при лимфопролиферативных заболеванияхunclassified
“…[NM 003258] TK1-Thymidine kinase 1, soluble is a cytoplasmic enzyme. Studies have shown that in patients with primary breast cancer, high TK values were shown to be an important risk factor in nodenegative patients and seemed to be associated with beneficial effect of adjuvant chemotherapy [28]. [NM 003239] TGFB3-transforming growth factor, beta 3 is a potent growth inhibitor of normal epithelial cells.…”
Section: Appendix: Biological Evidencementioning
confidence: 99%